A Taxonomy of Network Intrusion Detection System for Wireless Communication - Karthik, R; Shivakumar, BL (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, it is essential to give a high-level security to protect highly sensitive and private information. Network Technology and Internet Application sector plays a vital role in today’s trend. Over a few years, we are able to see a tremendous growth towards the network technology. With the help of internet facility, we are able to carry out different tasks such as internet banking, online education, social networking and so on, which make our life more comfortable. Numbers of clients are being connected with the technology day by day. Despite being hacked by unwanted intruder or malicious.This cause a great damage to the documents, software and the confidential data’s. Terms such as worms, viruses and Trojans create fear in the internet clients. Because of security and safety against these acts, it can be done only with our system, which will be able to sense and reply these attack or penetration. A very helpful tool in this is Intrusion Detection System (IDS), which detects the attacks and analysis it to take appropriate decision against it. Intrusion Detection System has a great impact on cyber security and network vulnerability. Once the detection is marked, the corresponding action could be taken by IDS. Intrusion detection system is a softwareand hardware device. This paper will illustrate us an overview of IDS and to create a secure zone in the sector of networking. Furthermore, appropriate problems and challenges in this field are consequently illustrated and discussed.